Agri-business in the rural sector: Scope and challenges of incubation - K, Muralidharan; S, Jayasekhar; M, Jaseem Shakeel; Singh, Vikram (Indian Farming, 2021)
In the agrarian sector, the focus has rapidly shifted from a production-oriented system to a farmer welfare one. Doubling the farm income by 2022 is the target fixed by the Indian Government. Promoting entrepreneurship among farmers through the formation of Farmer Producer Organisations is a thrust area of the government. The agricultural reforms ensure the farmers are freed to grow crop of their choice and sell anywhere in India. This changed scenario highlights the need for research reorientation, providing timely advisories to farmers, providing market intelligence, and continuous innovation in post-harvest handling. Nevertheless, shifting away from a production-oriented regime, the sector, of late, had confronted with newfound challenges, especially the dwindling farm income. Hence, it is imperative to provide the farmer opportunities to upgrade himself from a food provider to an entrepreneur. Introducing the concept of Business Incubation in our NARES has been pertinent in view of the shifting dynamics experienced in the agricultural sector. A very important group of people, entrepreneurs, became important stakeholder of the system. Although the primary objective of Kalpa ABI is to promote entrepreneurship with selected business models using proven and potential technologies developed at the Institute; as it is reflected from the activities of ABI, the most significant achievement is its large customer base that includes a large number of entrepreneurs especially the rural youth who are in continuous proximity of the Institute to understand the scope as well as the intricacies of starting an Agri- Business. It is highly appreciable that the reforms and policies envisaged by the government have the right focus to address the livelihood of our farmers and agri-business aspirants, and in the present context, the major challenge is developing an equitable and sustainable plantation sector that ensures inclusive growth and international competitiveness.